PENGARUH FAKTOR KARAKTERISTIK PETANI DAN METODE PENYEMPROTAN TERHADAP KADAR KOLINESTERASE - Yeviana Dwi Rahmawati (The Indonesian Journal of Occupational Safety and Health, 2017)
The farmers' efforts to reduce pests are using pesticides. But, there is an adverse effect farmer’s health, namely pesticide poisoning. Based on Litbang (2004), the incidence of poisoning were about 80% in the developing countries. The purpose of this study is to analyze factors which are affected with cholinesterase levels of rice farmers who sprayed pesticides in Sumberejo, Kecamatan Balong Kabupaten Ponorogo. This study used an observational study design with cross sectional analytic. The sample was all rice farmers who sprayed pesticides in rice plants between 1-7 days before they blood was taken for examination of the enzyme cholinesterase. Total respondents are 40 farmers. The study was in Sumberejo, Kecamatan Balong Kabupaten Ponorogo in July 2013-February 2014. Variables in this study were age, education level, knowledge level, smoking status, used of PPE, work period, the last spraying, direction, time, and duration of spraying, and cholinesterase levels. The primary data was obtained by observation, interview, and spectrophotometer. The technique of data analysis is linier regression test. The results showed that the value of cholinesterase levels is between 5602 U/L-15668 U/L were categorized into moderate and normal. There are no affect characteristic factors (age and work period) on cholinesterase levels. Has affect method of spray (last of spraying) on cholinesterase levels.The conclusion was there is effect between the last of spraying on cholinesterase levels.Keywords: farmers, pesticides, cholinesterase levels